2015
DOI: 10.1089/neu.2015.3895
|View full text |Cite
|
Sign up to set email alerts
|

Acute Phase Proteins in Cerebrospinal Fluid from Dogs with Naturally-Occurring Spinal Cord Injury

Abstract: Spinal cord injury (SCI) affects thousands of people each year and there are no treatments that dramatically improve clinical outcome. Canine intervertebral disc herniation is a naturally-occurring SCI that has similarities to human injury and can be used as a translational model for evaluating therapeutic interventions. Here, we characterized cerebrospinal fluid (CSF) acute phase proteins (APPs) that have altered expression across a spectrum of neurological disorders, using this canine model system. The conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…An increase in CRP concentration in CSF is thought to largely result from blood‐brain barrier damage (ex. subarachnoid hemorrhage6 or vasculitis due to sepsis17); intrathecal production of CRP18 and disruption of glymphatic circulation may also contribute to a lesser extent 19. Even when the blood–brain barrier is intact CRP level in the CSF is directly related to serum CRP because this protein flows from blood into the cerebrospinal space,20 but determination of a CRP index along with IgG index has been proposed in cases of canine Steroid Responsive Meningitis‐Arteritis (SRMA)6 and may also be helpful in cases of blood–brain barrier disruption in equine neurological disease.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in CRP concentration in CSF is thought to largely result from blood‐brain barrier damage (ex. subarachnoid hemorrhage6 or vasculitis due to sepsis17); intrathecal production of CRP18 and disruption of glymphatic circulation may also contribute to a lesser extent 19. Even when the blood–brain barrier is intact CRP level in the CSF is directly related to serum CRP because this protein flows from blood into the cerebrospinal space,20 but determination of a CRP index along with IgG index has been proposed in cases of canine Steroid Responsive Meningitis‐Arteritis (SRMA)6 and may also be helpful in cases of blood–brain barrier disruption in equine neurological disease.…”
Section: Discussionmentioning
confidence: 99%
“…In dogs, an increase of Hp in the CFS was demonstrated in animals with naturally occurring intervertebral disc herniation (IVDH) compared to healthy dogs (Anderson et al 2015). In the same study, dogs with severe spinal cord injury showed significantly higher concentration of Hp in the CSF than animals with slight to moderate injuries.…”
Section: Discussionmentioning
confidence: 78%
“…A positive correlation was observed between the ceruloplasmin concentration in the CSF and the severity of spinal cord injuries in dogs with IVDH (Anderson et al 2015). Ceruloplasmin was also correlated with the concentration of total proteins in the CSF, signaling rupture of the brain-blood barrier.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations